2009
DOI: 10.1089/cap.2008.044
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Trial of Lithium in Youths with Severe Mood Dysregulation

Abstract: Objective The diagnosis and treatment of youth with severe nonepisodic irritability and hyperarousal, a syndrome defined as severe mood dysregulation (SMD) by Leibenluft, has been the focus of increasing concern. We conducted the first randomized double-blind, placebo-controlled trial in SMD youth, choosing lithium on the basis of its potential in treating irritability and aggression and neuro-metabolic effects. Methods SMD youths 7–17 years were tapered off their medications. Those who continued to meet SMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 89 publications
(96 reference statements)
0
84
0
2
Order By: Relevance
“…So far, the only clinical trial in SMD is a pilot study of lithium, which was not effective. 25 Additional treatment trials in youth with severe, nonepisodic irritability are a pressing public health need, given that an SMD proxy phenotype occurred with a prevalence of 3.3% in an epidemiologic sample in the United States 9 and mood lability occurred in more than 5% of the population of children and adolescents in a sample in the United Kingdom. 26 Although it is important to frame the question, "Is SMD a developmental presentation of BD?"…”
Section: Discussionmentioning
confidence: 99%
“…So far, the only clinical trial in SMD is a pilot study of lithium, which was not effective. 25 Additional treatment trials in youth with severe, nonepisodic irritability are a pressing public health need, given that an SMD proxy phenotype occurred with a prevalence of 3.3% in an epidemiologic sample in the United States 9 and mood lability occurred in more than 5% of the population of children and adolescents in a sample in the United Kingdom. 26 Although it is important to frame the question, "Is SMD a developmental presentation of BD?"…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Smaller hippocampal volumes are among the most replicated neuroimaging findings in patients with major depressive disorder compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies have predominantly shown no changes in brain NAA levels during Li treatment. [8][9][10][11] A single prospective study reported a small NAA increase after 4 weeks of Li treatment, 3 whereas another investigation found an NAA decrease after 6 weeks of Li exposure. 12 Cross-sectional studies have also been inconsistent, with reports of greater 13,14 as well as comparable [15][16][17] brain NAA levels in Li-treated versus control participants.…”
Section: Introductionmentioning
confidence: 99%